TINGKAT KEPUASAN KONSUMSI PENGGUNA SHOPEE DALAM PERSPEKTIF EKONOMI ISLAM - Eka Putri Salsabilla; Silviana Pebruary (Jurnal Rekoginisi Ekonomi Islam, 2023)
This research was conducted to explain the level of consumer satisfaction of Shopee users from an Islamic economic perspective. Satisfaction is an evaluation of a reaction resulting from consumption and perceived deviations in performance or action as a result of failure to meet expectations. The data analysis method used is qualitative analysis with source triangulation. Collecting data used in this study by using interviews, questionnaires and documentation. The results of this study indicate that consumer satisfaction in shopping through Shopee is obtained through percentages and rating the level of consumer satisfaction with Shopee users.